El compromiso limitado. Un estudio sobre las razones estratégicas e identitarias de las acciones de resistencia y compromiso en el trabajo - LEÓN MEDINA , Francisco José (Cuadernos de Relaciones Laborales, 2010)
In this paper we present a case study based on eighteen interviews conducted with workers from an automotive multinational company. Unlike the dominant conceptions of labour process studies, we will hold that, at least for this case, the combination of actions of resistance and commitment cannot be interpreted as a manifestation of a “colonized” and “contradictory” subjectivity. On the contrary, workers’ patterns of behaviour seem to be caused by an identity-based rationality, and the decision about the visibility or invisibility of each one of those actions seems to be caused by a strategic rationality. Our study suggests the necessity of the labour process ethnographical studies to begin with an assumption of production agent’s rationality. Even though they should consider that there can be different kinds of rationality conditioned by the context of its gestation and expression.